Computer-related risks - Neumann, Peter 1932- (ACM Press, 1995)
This book is much more than a collection of computer mishaps; it is a serious, technically oriented book written by one of the world's leading experts on computer risks. The book summarizes many real events involving computer technologies and the people who depend on those technologies, with widely ranging causes and effects. It considers problems attributable to hardware, software, people, and natural causes. Examples include disasters (such as the Black Hawk helicopter and Iranian Airbus shootdowns, the Exxon Valdez, and various transportation accidents); malicious hacker attacks; outages of telephone systems and computer networks; financial losses and many other strange happenstances (squirrels downing power grids, and April Fool's Day pranks). Computer-Related Risks addresses problems involving reliability, safety, security, privacy, and human well-being. It includes analyses of why these cases happened and discussions of what might be done to avoid recurrences of similar events. It is readable by technologists as well as by people merely interested in the uses and limits of technology. It is must reading for anyone with even a remote involvement with computers and communications - which today means almost everyone.
Includes bibliographical references (pages 333-344) and index. - Print version record
Keywords: Computers -- Reliability; Computer security; Risk management; Ordinateurs; Fiabilité; Sécurité informatique; Gestion du risque; risk management; Computers; Reliability; Risikomanagement; Computer; Zuverlässigkeit; Computerbeveiliging